Understanding Fintech: Financial Technology Literacy - Endarwati Endarwati; Citra Ayudiati (Universitas KH. Abdul Chalim Mojokerto, 2024)
The rapid development of information and communication technology has significantly impacted the financial industry, particularly in financial services. This industry is no longer solely dominated by conventional financial institutions but has increasingly shifted toward financial technology based on Internet servers and applications. Women, as key members of their families, actively engage with financial markets and fintech, making them an important subject for research. Fintech encompasses products such as e-wallets, P2P lending, and crowdfunding. This study employs quantitative methods, using questionnaires as the primary data collection tool. Among the three fintech products, e-wallets were the most recognized and understood by respondents. This indicates that e-wallets are more easily accessible and comprehensible compared to other products.